Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $f:\mathbb{R} \rightarrow \mathbb{R}$ be a smooth function. Let $R$ be the radius of convergence of the Taylor series centered at $a.$ For each $n \in \mathbb{N},$ let $M_n= \sup\{f^{n}(t) : t \in (a-R, a+R)\}$ and assume $\displaystyle\lim_{n\to \infty}\frac{M_n}{n!}R^n < \infty.$

Show that $x \in(a-R, a+R) \implies \displaystyle\lim_{n\to \infty}\frac{M_n}{n!}(x-a)^n=0.$

I'm having a hard time figuring out what exactly is going on here. I wonder if someone could just help me understand why the above is true, without going into details about how to prove it.


share|cite|improve this question
up vote 1 down vote accepted

You are given that $\lim_n {M_n \over n!} R^n = L < \infty$. If $x \in (a-R,a+R)$, then $d=|x-a| < R$.

We have ${M_n \over n!} |x-a|^n = {M_n \over n!} d^n = {M_n \over n!} R^n ({d \over R})^n$.

Let $a_n = {M_n \over n!} R^n$, $b_n = ({d \over R})^n$. We are given that $a_n \to L$ and we see that $b_n \to 0$, hence $a_n b_n \to 0$.

share|cite|improve this answer
Thanks! You mean $x \in (a-R, a+R)$ in the first line. – user66360 Dec 8 '13 at 19:27
@kbball: Fixed it, thanks! – copper.hat Dec 8 '13 at 19:31

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.